2016
DOI: 10.1016/j.jeurceramsoc.2015.09.039
|View full text |Cite
|
Sign up to set email alerts
|

Effect of particle size on processing of bioactive glass powder for atmospheric plasma spraying

Abstract: The work addresses the effect of the particle size of a bioactive glass feedstock on the processing and microstructure of the resulting coatings obtained by atmospheric plasma spraying (APS). It was observed that the reduction of particle size negatively affects the flowability of the powder. In addition the thermal behaviour (weight losses, glass transitions, crystallisations, etc) also depended on the particle size of the glass powder.No coating was obtained with the coarser fractions (higher than 200 µm) du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 24 publications
0
19
0
2
Order By: Relevance
“…These particles exhibit smooth surface and regular sphere shape with a diameter ranging from 3 to 22 μm, which is suitable for spray as reported. 15 Alumina (96% in purity, thickness of 1 mm) with surface roughness about 0.3 μm to form adhesive layer was used. 16,17 The metallization of alumina substrate was carried out using a Micro-Nanoparticle Coater-1700013 (CMD-PA60, Inocon Technologie GmbH, Austria).…”
Section: Powders and Coating Processmentioning
confidence: 99%
“…These particles exhibit smooth surface and regular sphere shape with a diameter ranging from 3 to 22 μm, which is suitable for spray as reported. 15 Alumina (96% in purity, thickness of 1 mm) with surface roughness about 0.3 μm to form adhesive layer was used. 16,17 The metallization of alumina substrate was carried out using a Micro-Nanoparticle Coater-1700013 (CMD-PA60, Inocon Technologie GmbH, Austria).…”
Section: Powders and Coating Processmentioning
confidence: 99%
“…This glass powder was obtained by the melting and quenching method [17]. To prepare the suspension, the glass powders were mixed with DGME solvent (Dowanol DPM, Dow Chemical, USA) with a proportion of 10 vol.% of solids and 90 vol.% of solvent, employing 0.5 wt% (relative to solids content) of D190 (Disperbyk-190, Byk, Germany) as a dispersant agent to stabilise the suspension.…”
Section: Synthesis and Characterisation Of The Bioactive Glass Suspenmentioning
confidence: 99%
“…In a recent paper with APS-BG coatings, the authors have shown that the abundance of round pores in the microstructure of these coatings is consequence of a liquid phase sintering mechanism operating during the thermal treatment of glassy particles [17]. For this reason, the SPS feedstock characteristics are expected to strongly affect the liquid phase sintering of the as-sprayed glass particles as well as on the evolving of gas bubbles occurring during the rapid sintering of melted glass particles.…”
Section: Introductionmentioning
confidence: 99%
“…CaO and 24.0 Na2O (in oxide wt%) was obtained by melting and quenching, as previously reported [24]. Then, the glass was dry milled in a hammer mill and sieved to obtain a powder with a particle size lower than 63 µm.…”
Section: Feedstocks Preparation and Characterisationmentioning
confidence: 99%